INTRODUCTION - Cárdenas Beltrán Melba Libia (Universidad Nacional de Colombia, 2000)
We perceive teachers to be agents of change who are characterised by high selfesteem as well as by cultural and professional identity. Likewise, we suppose teachers possess solid knowledge of their teaching fields and abilities to identify problems as well as to provide solutions to them within particular educational contexts. For those reasons, and in order to help teachers strengthen their professional knowledge, the programmes offered to English teachers in the Foreign Languages Department of the Universidad Nacional de Colombia since 1995 have included three main components: language development, methodological updating and classroom research. The first two components respond to the trainees' manifested needs to maintain or improve competence in using and teaching the target language, whereas the last one attempts to foster innovation.